The Influence Public Knowledge and Perception Regarding Use Alternative Energy Sources Based Biofuels - Evita Anggereini; Rina Aprianti Nainggolan; Mia Aina (Jurnal Penelitian Pendidikan IPA, 2023)
Indonesia is one of the countries that depend on fossil-based fuels as a good source of energy. Until now, the portion of fossil energy use has reached more than 80% in the national primary energy mix. From these data, it is clear that dependence on fossil energy in Indonesia is still high. This study aims to describe the knowledge and perceptions of the people of Jambi City about the prospect of using alternative energy sources based on biofuels. And to find out whether there is an influence between knowledge and people's perceptions of Jambi City about the prospect of using biofuel-based alternative energy sources. This study uses the type of mix method. The instruments used in this study were questionnaires and interviews. The results obtained are that the community perception value in Jelutung sub-district regarding biofuel-based alternative energy is higher than the community in Pasar Jambi sub-district. People in Pasar Jambi Sub-district have knowledge about alternative energy based on biofuel which is superior to people in Jelutung sub-district